Art through the ages : Eight edition II renaissance and modern art - Gardner, Helen, 1878-1946. (San Diego : Harcourt Brace Jovanovich, 1986)
A standard adult history of art that has often been revised since its first publication in 1926.
Cover title: Art through the ages.
Includes index.
Bibliography: p. 984-991.
Keywords: Art -- History